The Effect of Image-Schema-Based Instruction on Learning/ Acquiring Polysemous Prepositions - BOUCHENEK, Hasna Lamis (Journal of Human Sciences, 2017)
Polysemous prepositions represent a real challenge for students and teachers alike. The many meanings of these words have always been pedagogically treated in a piecemeal fashion and as largely arbitrary. This makes their learning more complicated because learners keep on experiencing difficulty with their semantics. However, the use of a new way to teach polysemous prepositions such as applying image-schemas seems to be very promising. This paper aims at presenting the characteristics of the semantics of polysemous prepositions and reports on an experimental study which examines the efficacy of image-schema-based instruction on learning the semantics of the English prepositions above, across, in, on, out, over and through. It also investigates the students’ attitudes towards the usefulness of this form of instruction. Eighty students studying English as a foreign language at the University des Fréres Mentouri, Constantine were chosen randomly. They were divided into a Control Group and a Treatment Group. Comparisons of pre-test and post-test results show that the group who received instruction based on image-schemas experienced a dramatic change in their understanding of the semantics of the target prepositions. On the basis of the results of the students’ questionnaire and experiment, it can be deduced that image-schema-based instruction plays an important role in improving the learning of polysemous prepositions, and it can serve as a vital tool in teaching them.